Analisis del impacto de la educación gratuita en las universidades estatales de la ciudad de Guayaquil - Machasilla Morquecho, Erika (2009)
The approbation of the Educational Plan through the popular consult of the 26 of November of 2006, where it determined that the education is free in all its levels, it has constituted since a beginning motive of continues debates and confrontations between students and the government about its viability. The economic reality of the Ecuador revels us a high volatility of the GIP’s grow, which don’t permit to guarantee a budget that carry out with the established on the Constitution. This paper describes and analyses the evolution of the public expenses in the educative sector. Subsequently, it determines econometrically if the arguments in favour of the intervention of the State on the superior education, that is to say, if this social inversion will generate greater social yields than privates. Through of this analyze we pretend to demonstrate if the free education is synonymous of quality, as the general argument is the more expenses, the better education. It gives more importance to the sum which is destine to the education, as a form of keep pleased to a sector of the society and not look for more effective and viable mechanics with the national reality of the country, such as to fortify the student loan instead of giving free education, since this will multiply of fair and equitable way the possibilities of building a society more competent who contribute to the economic and social development o f our country.